(untitled) (REMUNOM, 2024)
The general objective of the research is to discuss the possibility of applying the principle of insignificance in the crime of drug trafficking. To carry out the research, the methodological procedure of bibliographic and documentary review with a qualitative approach was used, in which the scientific articles, theses and dissertations consulted in the construction of the work were found in digital repositories, such as Google Scholar, Scielo and BDTD. Through the work, it was possible to understand that the majority understanding of the doctrine and controversy believes that it is not possible to apply this principle to trafficking, as it is a crime of abstract danger, which does not require proof of harm to declare the damage caused by the conduct. However, as granted, this understanding is applied in the courts automatically, disregarding the characteristics of the specific case, disproportionately and completely inconsistent with the principles of Criminal Law, such as the principles of reasonableness, harmfulness and minimum intervention